An exploratory clinical trial of bortezomib in patients with lower risk myelodysplastic syndromes. Issue 7 (9th June 2017) - Daher, May; Hidalgo Lopez, Juliana Elisa; Randhawa, Jasleen K.; Jabbar, Kausar Jabeen; Wei, Yue; Pemmaraju, Naveen; Borthakur, Gautam; Kadia, Tapan; Konopleva, Marina; Kantarjian, Hagop M.; Hearn, Katherine; Estrov, Zeev; et al.
Abstract: Myelodysplastic syndromes (MDSs) are characterized by ineffective hematopoiesis and an increased risk of transformation. Few effective therapies are available for lower risk MDS patients, especially after the failure of hypomethylating agents. MDS progenitor cells are dependent on the nuclear factor‐κB (NF‐κB) for survival, which makes it an attractive therapeutic target. As a proteosomal inhibitor, bortezomib is thought to have inhibitory activity against NF‐κB. We designed a proof‐of‐principle study of subcutaneous (SC) bortezomib in lower risk MDS patients with evidence of NF‐κB activation in their bone marrow. Fifteen patients were treated, their median age was 71 (range 56–87), 33% were low and 67% int‐1 by IPSS, median number of prior therapies was 2, all patients were transfusion dependent. Baseline median pp65 percentage was 31% and 11 patients had evidence of ring sideroblasts (RS). SC bortezomib was safe, well tolerated with no excess toxicity. Three patients out of the 15 (20%) had evidence of response with hematologic improvement (HI‐E). Bortezomib caused a decrease in pp65 levels in 7 out of 13 evaluable patients (54%, P  = .025). Of interest, unexpectedly, we observed a significant decrease in RS in 7 out of 10 (70%) evaluable patients during treatment. In conclusion, this study suggests that NF‐κB activation, measured by pp65 levels, may be a useful biomarker in MDS. Bortezomib is safe in this patient population but has modest clinical activity. The role of the proteasome in the genesis of RS needs further study.